2020
DOI: 10.1186/s13690-020-00515-x
|View full text |Cite
|
Sign up to set email alerts
|

Parent-young communication on sexual and reproductive health issues and its association with sex and perceptions of young people in Ethiopia, 2020: a systematic review and meta-analysis

Abstract: Background There is no national representative and conclusive data regarding parent-young communication. Therefore, this study aimed to estimate the pooled prevalence of parent-young communication on sexual and reproductive health issues and its association with sex and perceptions of young people about its importance in Ethiopia, 2020. Methods The Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) was used during systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Two-thirds of Adolescents had never talked to their parents about ASRH issues. Similar study findings were reported from a systematic review, where the pooled prevalence of adolescent-parent communications in Ethiopia is found to be only 43% [56]. However, adolescents who had discussions on ASRH issues with their parents were 4.5 times more likely to use the services [AOR = 4.53 (2.52-8.16)] compared to those who had not.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Two-thirds of Adolescents had never talked to their parents about ASRH issues. Similar study findings were reported from a systematic review, where the pooled prevalence of adolescent-parent communications in Ethiopia is found to be only 43% [56]. However, adolescents who had discussions on ASRH issues with their parents were 4.5 times more likely to use the services [AOR = 4.53 (2.52-8.16)] compared to those who had not.…”
Section: Discussionsupporting
confidence: 84%
“…This finding is in agreement with other studies conducted in Harrar, Jimma, and Machakel. [32,51,[56][57][58]. The underlying reason might be that having discussions on ASRH issues may build adolescents' confidence and help them to expose their ASRH health concerns, understand consequences of SRH issues, and motivate them to use adequate services.…”
Section: Discussionmentioning
confidence: 99%
“…This statement is confirmed by Joorbonyan et al [54], who explain that parental knowledge, accurate information, and self-efficacy in providing sexual information are crucial components that enable adolescents to engage in HIV/AIDS prevention behaviors. Sexual communication between parents and adolescents reduces their vulnerability to negative peer influences to engage in sexual activity [11], [55]. The quality of communication about sex between parents and their adolescent children is uniquely correlated with adolescents' sexual behavior [56].…”
Section: Discussionmentioning
confidence: 99%
“…As per author's knowledge there is inadequate evidence about the proportion of parent-young people communication in Ethiopia (24), point prevalence varies among the studies and there is no established evidence at the study area. Moreover, there are inconsistent ndings with regard to proportion and factors associated with parent and young people communication on SRH issues.…”
Section: Introductionmentioning
confidence: 97%